Determinatezza nominale e aspetto verbale nella codifica della referenzialità: polisemia e ambiguità interpretative - Valentina Benigni; Lucyna Gebert (MediAzioni, 2023)
This paper examines the hypothesis that, in the languages which developed articles and in those which have grammaticalized the verbal aspect, the two categories perform similar functions in the coding of referentiality. In particular, the research is focused on the construction [Verb - Object] referring to so-called typical and usual events; it takes “READ THE NEWSPAPER” as an example, both in Italian and Russian. The contrastive analysis, based mainly on the comparable corpora of the Araneum family and, due to the scarcity of data, only partly on the Russian-Italian parallel corpus of the NKRJA, confirmed the hypothesis, at least as regards the construction under study. The investigation showed that in Italian there is a very strong correspondence between the [-referential] interpretation of the object and the definite article, while Russian exhibits a rather strong correspondence between the [-referential] interpretation of the object and the imperfective aspect. The assignment of a [± referential] value to the object nouns in Russian, a language without articles, and to nouns with the definite article in Italian, which in constructions referring to typical events receive a [-referential] reading, was based on context. In fact, in both languages, in order to identify the [± referential] status of nouns, it was necessary to take into account the temporal, modal, and actional characteristics of the respective verbs, the typical or occasional nature of the event, and the role of other elements of the sentence, such as adverbs or nouns that refer to customs and habits. The generalization resulting from the research can be extended to other typical events, mainly those referring to activities involving information, entertainment, and leisure, which are similarly marked with the definite article in Italian and the imperfective aspect in Russian. However, the notion of “typicality” turns out to be elusive, as it is strongly culture-specific and determined by the verbal and situational context.